The clinical diagnosis of equine sarcoids—Part 2: Assessment of case features typical of equine sarcoids and validation of a diagnostic protocol to guide equine clinicians in the diagnosis of equine sarcoids. (October 2018) - Haspeslagh, M.; Gerber, V.; Knottenbelt, D.C.; Schüpbach, G.; Martens, A.; Koch, C.
Highlights: The accuracy of the clinical diagnosis of equine sarcoids may be improved using a diagnostic protocol. A novel diagnostic protocol based on typical clinical features of sarcoids was critically assessed using an online test. The diagnostic protocol improved the diagnostic performance, especially for less experienced veterinarians. The diagnostic protocol may optimise case selection for diagnostic biopsies and decrease associated expenses and risks. Abstract: Research has shown that the accuracy of the clinical diagnosis of equine sarcoids (ES) can be improved. Particularly, less experienced veterinarians are often mistaken in their clinical judgement despite a high level of diagnostic confidence. The aim of this study was to develop and assess the performance of a diagnostic protocol (DP) to improve diagnostic accuracy and identify diagnostically challenging cases. The design of the DP was based on typical clinical features of ES and its algorithm was optimised through repeated tests on clinical cases prior to validating its performance in a representative online examination. A total of 22 equine practitioners and 31 veterinary students used the DP to diagnose 40 standardised ES and non-ES cases in an online examination. Scores of these 53 respondents were compared to scores of 128 respondents of comparable levels of expertise, and 14 experts, all assessing the same cases without using the DP. Overall, respondents using the DP were significantly more likely (odds ratio (OR) 1.25; 95% confidence interval (95% CI) 1.09–1.43) to diagnose a case correctly compared to respondents not using the DP and felt significantly more confident of their diagnosis (OR 1.53; 95% CI 1.39–1.67). Thus, the DP proved to be a reliable tool to increase clinical diagnostic accuracy and diagnostic confidence. The DP algorithms may be further improved with experiences gained from its application in equine practice and clinicians will be able to optimise their diagnostic accuracy and selection of lesions requiring a biopsy.